Order in International Finance, the Promotion of IMF Stand-By Arrangements, and the Drafting of Private Loan Agreements. Joseph Gold - Gold, Joseph (International Monetary Fund, 1982)
Examina algunos aspectos relacionados con el Orden Financiero Internacional y el papel que juega el FMI.